2020
DOI: 10.1186/s13048-020-00648-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum exosomal microRNA-34a as a potential biomarker in epithelial ovarian cancer

Abstract: Background: Ovarian cancer (OC) is a leading cause of cancer-related death in women, and thus an accurate diagnosis of the predisposition and its early detection is necessary. The aims of this study were to determine whether serum exosomal microRNA-34a (miR-34a) in ovarian cancer could be used as a potential biomarker. Methods: Exosomes from OC patients' serum were collected, and exosomal miRNAs were extracted. The relative expression of miR-34a was calculated from 58 OC samples by quantitative real-time polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…miRNA-21, miRNA-29a, miRNA-92, and miRNA-93 were significantly overexpressed in EOC serum samples compared to tissue samples, while other sets of miRs (miRNA-99b, miRNA-127, and miRNA-155) were underexpressed in serum samples compared to tissue samples of EOC patients (Resnick et al, 2009;Hausler et al, 2010;Deng et al, 2017). Maeda et al (2020) recently described the potential role of serum miRNA-34a in early diagnosis of ovarian cancer and for histological subtyping of EOC. The expression of serum miR-34a was significantly higher in ovarian carcinoma compared to normal control (Maeda et al, 2020).…”
Section: Blood-based Circulating Mirna As a Biomarker In Ovarian Cancmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA-21, miRNA-29a, miRNA-92, and miRNA-93 were significantly overexpressed in EOC serum samples compared to tissue samples, while other sets of miRs (miRNA-99b, miRNA-127, and miRNA-155) were underexpressed in serum samples compared to tissue samples of EOC patients (Resnick et al, 2009;Hausler et al, 2010;Deng et al, 2017). Maeda et al (2020) recently described the potential role of serum miRNA-34a in early diagnosis of ovarian cancer and for histological subtyping of EOC. The expression of serum miR-34a was significantly higher in ovarian carcinoma compared to normal control (Maeda et al, 2020).…”
Section: Blood-based Circulating Mirna As a Biomarker In Ovarian Cancmentioning
confidence: 99%
“…Maeda et al (2020) recently described the potential role of serum miRNA-34a in early diagnosis of ovarian cancer and for histological subtyping of EOC. The expression of serum miR-34a was significantly higher in ovarian carcinoma compared to normal control (Maeda et al, 2020). Similarly another study using High-throughput sequencing revealed 65 differentially expressed miRNAs (34 upregulated and 31 downregulated) in OC patients compared to healthy patients.…”
Section: Blood-based Circulating Mirna As a Biomarker In Ovarian Cancmentioning
confidence: 99%
“…Ovarian cancer is the deadliest gynecological cancer in women; hence, the early detection and treatments are vitally important (40). Efforts have been taken to developed drugs to treat ovarian cancers overexpressing estrogen receptor (ER) and HER2.…”
Section: Pretargeted Theranostics In Ovarian Cancermentioning
confidence: 99%
“…In contrast, miR-21 and miR-324 within these tumor-released exosomes were found to be strong neuritogenic signals [ 78 ]. miR-34a is a candidate biomarker for ovarian cancer and has been shown to correlate with tumor stage and aggression [ 79 ]. Additionally, miR-21 has been identified as a biomarker of chemotherapy response in esophageal, lung, pancreatic, and prostate cancers [ 80 , 81 , 82 , 83 ].…”
Section: Neurogenic and Oncogenic Trophic Factors As Biomarkers Ofmentioning
confidence: 99%